THE LATITUDE DISTRIBUTION OF SEISMICITY AND THE ROTATION OF THE EARTH - Levin B.V.; Chirkov E.B. (My University, 2000)
This paper examines the latitude distribution of the number and energy of earthquakes based on the NEIC catalogs (1900-1993). Some features were identified in the latitude distribution of seismicity that are related to the rotation of the Earth. The histograms showing the total number and energy of earthquakes as a function of the latitude (90°N to 90°S) demonstrated that the latitude distribution of the number of events N(φ) was similar to the curve describing the function R2(φ) or I(φ), where R is the distance to the axis of rotation and I is the moment of inertia of an element of the crustal layer. A well-defined local peak was discovered in the number of earthquakes around the so-called "critical parallel" 35°N introduced by A. Veronne (1912) and theoretically substantiated by F. N. Krasovskii and V. A. Magnitskii (1941). Comparison of the latitude distribution of seismicity between the eastern and western hemispheres showed that most of the local peaks in one of them coincided with local lows in the other, and vice versa. These features confirm the existence of an axial symmetry of the seismicity and corroborate a relation between the seismicity and rotation of the Earth.